High-density lipoprotein cholesterol subfractions in collegiate female volleyball players - Oda, K.; Miyahara, K.; Matsuo, K.; Mizuno, S.; Imamura, H. (Journal of Athletic Enhancement, 2017)
Much of the published data on the lipid profiles of athletes are based on studies of endurance athletes. Data on female volleyball players are rare. The purpose of this study was thus to examine serum high-density-lipoprotein cholesterol (HDL-C) subfractions in collegiate female volleyball players. Twenty-six female collegiate volleyball players were compared with 26 age- and body mass index-matched control subjects. Dietary information was obtained with a food frequency questionnaire. The subjects were all nonsmokers and were not taking any drug known to affect lipid and lipoprotein metabolism. The volleyball players showed significantly higher mean HDL2-C than the control group. There were no significant differences in HDL-C and HDL3-C between the 2 groups. The results indicate that favorable lipid and lipoprotein profiles could be obtained by vigorous volleyball training and significantly higher HDL2-C could be obtained without observing significant differences in HDL-C and HDL3-C.